The investigation of dominated anaerobic bacteria throughout degradation of a raw antibiotic Industry wastewater - Delia T Sponza; Nefise Erdincmer (Annals of Systems Biology - Peertechz Publications, 2020)
In recent years, it was found that the COD and antibiotics in the antibiotic industry wastewaters can not be effectively removed with conventional biological treatment processes [1]. The experiences performed with advanced treatment processes (Hydrogen peroxide and fentone) showed low antibiotic yields and high cost [2-5] showed that tetracyline antibiotic concentrations between 0-50 mg/l decrease the methane gas productions.